Práticas declaradas por professores e gestores sobre o ensino de matemática: estudo de uma escola com alto índice na Prova Brasil - Thomé, Roberto Jefferson (2020)
This research has as general objective to identify and understand the declared practices of polyvalent teachers and managers about the teaching of mathematics in a municipal public school in the city of Rio Claro in the interior of the state of São Paulo, which presents high rates in external evaluations. The theoretical analysis of this work was based on the related themes on the theme and in Tardif (2014) and Gauthier (2013) on teaching knowledge, in Shulman apud Mizukami (2004) on knowledge base and in Serrazina (1999), Pais (2013) and Nacarato; Mengali; Passos (2017) on Mathematics Education in the early years. A survey of the main legal documents related to the topic was carried out. Methodologically, the study was based on the qualitative interpretative approach. The research had the voluntary participation of twelve teachers and two managers of the selected school. For this, we used as a data collection instrument mixed questionnaires and semi-structured interviews. For data analysis, we used the data triangulation technique with the intersection of information and built the following categories: continuing education in mathematics, external evaluation, development of mathematics teaching challenges and possibilities in mathematics teaching, teacher training development. As a result of the triangulation of the interview data from the questionnaires, documents and theoretical contributions, we verified the declared practices of teachers and managers presented the following indications: development of simulations, training practices involving chess, development of reading practice for the resolution of problems at the Brazil Math Test, lower teacher turnover, knowledge sharing, development of school planning based on the data acquired at Brazil Tasting, with the development of logical reasoning activities and challenges, teaching materials available within the school environment. All of these indications may have contributed to the development of mathematics education and the results of the educational unit in the Basic Education Assessment System (SAEB). We also observed in these manifestations some challenges pointed out by teachers and managers, such as the lack of mastery of the content to be taught, the absence of courses focused on the area of mathematics, lack of knowledge to deal with the target audience of Specialized Educational Assistance (AEE) and the lack of space for sharing the knowledge of the experience. The results indicate the need for a continuous training policy focused on the area of mathematics for teachers and managers in the municipal network.